2003
DOI: 10.1126/science.1083430
|View full text |Cite
|
Sign up to set email alerts
|

Sensing DNA Damage Through ATRIP Recognition of RPA-ssDNA Complexes

Abstract: The function of the ATR (ataxia-telangiectasia mutated- and Rad3-related)-ATRIP (ATR-interacting protein) protein kinase complex is crucial for the cellular response to replication stress and DNA damage. Here, we show that replication protein A (RPA), a protein complex that associates with single-stranded DNA (ssDNA), is required for the recruitment of ATR to sites of DNA damage and for ATR-mediated Chk1 activation in human cells. In vitro, RPA stimulates the binding of ATRIP to ssDNA. The binding of ATRIP to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
2,357
2
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,418 publications
(2,450 citation statements)
references
References 37 publications
76
2,357
2
15
Order By: Relevance
“…RPA is a protein complex that associates with single-stranded DNA (ssDNA) and is required for the recruitment of ATR-ATRIP complex to DNA damage. Moreover, the presence of RPA on ssDNA is sufficient to recruit ATR-ATRIP complex to DNA (Zou and Elledge, 2003). Thus, RPA was used as an indication for the induction of the ATR pathway.…”
Section: Resultsmentioning
confidence: 99%
“…RPA is a protein complex that associates with single-stranded DNA (ssDNA) and is required for the recruitment of ATR-ATRIP complex to DNA damage. Moreover, the presence of RPA on ssDNA is sufficient to recruit ATR-ATRIP complex to DNA (Zou and Elledge, 2003). Thus, RPA was used as an indication for the induction of the ATR pathway.…”
Section: Resultsmentioning
confidence: 99%
“…4 The potential interaction between ATM and RPA phosphorylation In this study, it has been found that ATM acts an early regulator rather than ATR-Chk1 in response to thymidine treatment-induced DNA replication stress in hTERT-NHU cells. Although RPA has already been reported to coat ssDNA and recruit ATR to trigger ATR-CHK1 checkpoint signalling pathway during replication stress (Zou and Elledge, 2003), it remains unclear that whether RPA is also involved in ATM-dependent checkpoint cascades. Here I showed that the ATM inhibitor is able to suppress RPA Ser4/8 phosphorylation directly under these conditions, suggesting that the ATM signalling pathway may participate in this phosphorylation although the deficiency of RPA Ser4/8 phosphorylation is most likely due to the failure such cells to enter S-phase.…”
Section: Chapter 6 Discussionmentioning
confidence: 99%
“…CHK1 is largely activated in response to ssDNA formation due to occurrence of functional uncoupled DNA polymerase and MCM helicase following replication inhibition (Byun et al, 2005). This ssDNA is rapidly coated by RPA which then recruits ATR through the ATR interacting protein (ATRIP) (Zou and Elledge, 2003). The formation of this complex activates downstream CHK1 through phosphorylation at Ser345 and Ser317 (Green et al, 2000;Zhao and Piwnica-Worms, 2001).…”
Section: Figure3 2a Gemcitabine Induces No Apoptosis In Htert-mentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption or attenuation of this response plays an essential role in promoting tumorigenesis (Lengauer et al, 1998;Hoeijmakers, 2001;Schar, 2001;Rouse and Jackson, 2002). Stalled replication forks are sensed by replication protein A (RPA)-mediated ATR (ATM-and Rad3-related kinase) recruitment to DNA damage-induced nuclear foci (Zou and Elledge, 2003). ATR and its related ATM kinases play central roles in the amplification of double-stranded break (DSB) signals, coordination of DNA damage repair and activation of cell cycle checkpoints (Zhou and Elledge, 2000;Shiloh, 2003).…”
Section: Introductionmentioning
confidence: 99%